Vegetation and flora in the vicinity of salt and brine extraction sites in the western part of Kuyavia (Poland) - Karasińska, Wiesława; Nienartowicz, Andrzej; Kunz, Mieczysław (Ecological Questions, 2023)
The paper presents a syntaxonomic and floristic analysis of salt marshes formed at the soda factories in Mątwy and Janikowo, the salt mine in Góra, and the salt works and spa hospitals in Inowrocław. In the study area delineated in this region, the analysis also covered salt marshes formed in places of failure of pipelines supplying brine to industrial, medical and recreational facilities, as well as those discharging saline industrial and municipal wastewater were also analysed. A total of 611 relevés were taken using the Braun-Blanquet method in 215 inland salt marshes occurring in the study area during four consecutive growing seasons (1998-2001). A numerical classification of this set of relevés and of 124 taxa of vascular plants recorded in these relevés was carried out using TWINSPAN. Taxa from the prepared floristic list were assigned to five geographical and historical groups, and the percentage of species of these groups was determined for the saltmarsh flora of the study area. It was found that most of the groups of relevés distinguished at successive levels of hierarchical divisive classification, performed based on differential species, correspond through their species composition to six (out of seven) syntaxa of halophytic vegetation distinguished in the studies conducted about 40 years ago in the entire area of Kuyavia. Of the total number of 124 taxa, 14 species of halophytes were identified, including six obligate and eight facultative ones. The number of taxa in the geographical and historical groups was as follows: 22 spontaneophytes, 73 apophytes, 16 archaeophytes and six kenophytes. No diaphytes were found in the study area, however, seven species of cultivated plants were recorded.